Estimating Active Case of Infectious Disease Using Seird Model; Case of Covid-19 Diseases in Malaysia - Azrul Azim Mohd Yunus; Shahrina Ismail; Arif Asraf Mohd Yunus; Muhammad Safwan Ibrahim; Shaharudin Ismail (Akademia Baru Publishing, 2026)
Indexed by SCOPUS / MYCITE